Factor Analysis of the Influence of Tax Knowledge and Taxpayer Awareness on Individual Taxpayer Compliance at KPP Yogyakarta - Uum Helmina Chaerunisak; Sri lestari Yuli Prastyini; Roban (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The aim of this research is to determine the influence of tax knowledge and taxpayer awareness on individual taxpayer compliance. The theoretical basis used is attribution theory. This type of research is quantitative. Primary data and secondary data were used to collect data by conducting surveys and distributing questionnaires to KPP Yogyakarta taxpayers. The sampling technique in this research was purposive sampling. Data collection was carried out by distributing the Google Form link via WhatsApp social media. The number of questionnaires processed was 100 respondents. The results of this research indicate that tax knowledge and taxpayer awareness have a positive effect on individual taxpayer compliance at the Yokyakarta Tax Service Office.